TINJAUAN YURIDIS TENTANG JAMINAN BAGI KELAYAKAN KAPAL UNTUK BERLAYAR ( KAPAL PERAIRAN DARATAN DI SAMARINDA ) - Delitani Damanik (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTTo the requirements of the classification certificate issued by the Bureau of Classification Indonesia for inland waterway vessels are included in the provisions of Instruction of the Minister of Transportation No. IM.8 / 407 / PHB-81 which ships a length of 20 m or more or 100 GT to on or driven by the engine power of 150 HP to the top, just handed guidance and oversight to the Office of the Ministry of Transportation of East Kalimantan province, so that the owner or entrepreneur docks and shipyards and shipping companies not to pay too much, but it is not comparable with the manufacture and development inland waterways vessels concerned. So therefore, coaching, guidance and oversight for the feasibility in terms of ship construction sufficient submitted and carried out by the Regional Office of the Department of Transportation of East Kalimantan province along with the associated apparatus. Steps that can be taken with regard to accountability entrepreneurs inland waterways transport vessel is as follows: It should be set out more about the responsibilities of employers freight inland waterways, particularly those dealing with restrictions on the amount of compensation; Prior made the rules governing the limitation of the amount of compensation, it would need to be held research regarding restrictions or amount of compensation to be paid in the form of standard or minimum limit corresponding to the sense of justice in society. Against the transport of persons deemed necessary to include a sentence "that beneficiaries Raharha Insurance Services does not eliminate the right of transport service users or their heirs to obtain compensation from the carrier" in the coupon coverage.